Contemporary themes in early childhood education and international educational modules - Licardo, Marta; Simões Dias, Isabel (2019)
The purpose of the book is to present contemporary themes in early childhood education that are important for preschool education in practice and as topics in the education of students who will work in preschool education settings. The presented scientific research includes various themes in the field of pedagogy, didactics, special didactics and psychology. The results of the research reveal important conclusions regarding relationships between children and preschool teachers, children’s relationships with peers, important practices for social-emotional learning, problems that occur in students’ mathematics knowledge and the possibilities of promoting family literacy. Professional reports present international good practices in various educational settings for preschool education students. The presented good practices are innovative and are all based on socio-constructivist pedagogies. Authors report on how to activate learning in early childhood education with service learning, programming with children, science technology and maths, daily training in kindergartens, multimodal literacy, dance and didactic materials. In the last chapter international educational modules are presented that were prepared and tested within the project Erasmus+: International Learning Module in Early Years Education (EYE), between the years 2017 and 2019. These modules are examples of innovative education and how to integrate important topics in international early childhood education.
Keywords: early childhood education; international modules; pedagogy; didactics; special didactics